Human Geography - Rosenfeld, Christine; Burtch, Nathan (Open textbook library., 2023)
Welcome to Human Geography! If you are interested in how humans interact with the environment and how human systems are geographically distributed over space, then you’ve found your place. We hope that find this textbook useful and enjoyable; please dive in by clicking “Contents” to immerse yourself in all-things-human geography.